Britain and the Origins of the Vietnam War - Smith, T. author. aut Link
XIII, 229 p.
Keywords: British foreign policy towards Vietnam illustrates the evolution of Britain's position within world geopolitics, 1943-1950. It reflects the change of the Anglo-US relationship from equality to dependence, and demonstrates Britain's changing association with its colonies and with the other European imperial spheres within Southeast Asia.